METHODS OF CHOOSING PARENTAL PAIRS FOR CROSSES IN THE BREEDING OF SELF-POLLINATING CROPS FOR YIELD - S. B. Lepekhov (Труды по прикладной ботанике, генетике и селекции, 2018)
Proceedings on applied botany, genetics and breeding. Vol. 178. Iss. 4. SPb.: VIR, 2017. P. 80-93. Bibl. 82. The ecogeographical principle of choosing pairs for crossing developed by V. I. Michurin has appeared so effective that it is still used by many plant breeders. Meanwhile, as a result of extensive exchange of breeding material, this ecogeographical approach to the matching of pairs has lost its relevance, being replaced by the new methods of finding phenotypic and genotypic differences between parents. However, new mathematic methods have failed to win similar general recognition. This article reviews the basic methods of choosing parental pairs for crosses in self-pollinated crop breeding. Positive and negative aspects of using these methods in breeding practice are discussed. By now, many facts have been accumulated about the ability of lines in remote generations to reach the F1 yield level. An assumption is made that high-yielding lines may be selected from crosses with high yield in F1. Major problems of pair selection according to the degree of genetic distance between parents are highlighted. Methodical difficulties faced by breeders when they compare different pair selection principles are discussed.